Date Powder: From Production to Usage in Food Industry - Mihoubi, Mehdia; Mekri, Meriem; Meklati, Fawzi Rostane; Belhadj, Fatima Zohra Baghdad; Karaman, Safa; Toker, Omer Said (TAYLOR & FRANCIS INC, 2025)
Date palm (Phoenix dactylifera L.) is the most important fruit of the Arabian Peninsula. Date fruit is widely consumed as a fruit and food alternative by people of all ages due to its rich nutritional and functional content, special aroma and taste. In addition, its spread form is used with different food products. The best way to use date based products in many food products is its powdered form which is produced with different drying methods (sun, hot oven, vacuum, drum, spray drying, microwave, freeze drying) to increase the usage area of the date palm and ease transportation and increase shelf life. The influence of drying methods on the quality characteristics of the date powdered was explained in detail in this paper. In addition, studies related to the effects of the incorporation of date powder on the quality characteristics, nutritional and functional properties of the food products were reviewed. Studies indicated that date powder can be used as a replacer of sugar to some levels depending on characteristics of the end products and to improve nutritional and bioactive properties of the food products. Processing methods should be considered for obtaining the powder form with desired quality.
Keywords: Date palm; date powder; drying; sugar replacer; DACTYLIFERA L. CULTIVARS; GLASS-TRANSITION TEMPERATURE; PHOENIX-DACTYLIFERA; CHEMICAL-COMPOSITION; ANTIOXIDANT ACTIVITY; PHENOLIC PROFILE; PHYSICOCHEMICAL CHARACTERISTICS; FUNCTIONAL-PROPERTIES; MICROSTRUCTURAL PROPERTIES; NUTRITIONAL COMPOSITION; Food Science & Technology; Nutrition & Dietetics